Розвиток комплексних природничих досліджень в Україні - Денисик, Г. (Історико-географічні дослідження в Україні, 2019)
Розглянуто проблему виокремлення етапів і періодів у процесі пізнання природи України; виділено і обґрунтовано 3 етапи і 6 періодів: етап початкового пізнання природи (40 – 35 тис. років тому – ІV ст. до н. е.); етап опису природи (V ст. до н. е. – середина ХVІІ ст.) розділений на три періоди: античний (V ст. до н. е. – середина І тис. н. е.); літописний (кінець І тис. н. е. – ХІІ ст.); опису природи переважно західноєвропейцями (ХІХ – ХVІІІ ст.). Розгортання наприкінці ХVІІІ ст. експедиційних та індивідуальних досліджень природи України – то паростки нового етапу в розвитку природничої географії і природничих досліджень. Етап наукових пошуків (ХІХ – початок ХХІ ст.) буде детальніше розглянутий у наступній статті. Розгортання наприкінці ХVІІІ ст. експедиційних та індивідуальних досліджень природи України – то паростки нового етапу в розвитку природничої географії і природничих досліджень. The problem of distinguishing stages and periods in the process of knowledge of the nature of Ukraine was considered. The history of the development of natural sciences does not always coincide with the history of Ukraine’s development. Therefore, use the names of historical stages (ancient, medieval, new and new) in the process of knowing the history of the development of natural sciences unreasonably. Available literature and cartographic material and Internet resources give an opportunity in the process of knowledge of the nature of Ukraine to allocate 3 stages and 6 periods: the stage of initial knowledge of nature (40 - 35 thousand years ago - IV century BC); the stage of the description of nature (V in. BC - the middle of the XVII century) is divided into three periods: the ancient (V century BC - middle I millennium BC); annalistic (end of the 1st millennium BC - XII century); description of nature is mostly Western Europeans (XIX - XVIII centuries). The phase of scientific research (XIX - early XXI century.) Will be discussed in more detail in the next article. It is noted that at the end of the second stage, along with the descriptions of nature, elements of scientific research and exploration emerged as a result of which were the academic expeditions of 1768-1774 and the investigations of individual scientists: Academician of the St. Petersburg Academy of Sciences I. Guldenstedt describes the outputs of the crystalline rocks of the south of the Ukrainian shield (“crystalline strip” ), soil and vegetation; Academician of the same Academy V. Zuev gives a general description of the nature of the Middle Dnieper, the south of Pridneprovskaya Upland, for the first time (1782) describes glandular quartzites (“gland slate”) on the banks of the Ingults; “Father” of Polish geology and geography Stanislav Stashits at the end of the eighteenth century. conducted fruitful studies of the nature of Western Ukraine. It is concluded that the originality and scientific value of written, cartographic and other sources of the narrative stage consists not only in their originality and historicism, but also in the fact that they are written and published, except for the Ukrainian, representatives of almost all European countries, partly the Middle East and Middle Asia Ukraine and its nature knew the world around. Apparently, this can be explained by the absence of a coincidence in the course of historical development of Ukraine with the level of its descriptions in different periods: the non-signified Scythian Ukraine was described by the ancient authors, and the disparate medieval - Western-European. From Herodotus through the chronicles to Boplan - a general summary of descriptive stage. Deployment at the end of the ХVІІІ century. expeditionary and individual studies of the nature of Ukraine are the seeds of a new stage in the development of natural geography and natural sciences.